Kepemimpinan Kepala Desa Dari Sudut Pandang Masyarakat Dan Pemuka Agama Di Desa Tonusu Kecamatan Pamonapuselemba Kabupaten Poso - Ani Susanti; Slamet Riadi; Rizali Djaelangkara; Nurul Salsabila Alli; Ratna Pertiwi; Putri Oktaviani; Aura Aqila Muthiah; Hasriani Hamun; Husnul Fatimah; Dhiya Qolbi Salimah; Moh Rizwan (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The leadership of the Village Head is crucial for the success of the community empowerment program and for creating social balance in the village. This study is motivated by the need to understand the leadership role of the Tonusu Village Head, particularly in social and religious development. The purpose of this study is to assess the leadership of the Village Head from the perspective of the community and religious leaders in the church, who are an important part of the influential community in the village. The approach used in this study is qualitative, with in-depth interviews, participant observation, and documentation, which are then analyzed through documentation and qualitative descriptive analysis. This study uses four indicators proposed by Hamalik (2001:166) which include the Village Head as a Catalyst, Facilitator, Problem Solver, and Communicator.